2017
DOI: 10.18805/lr-3816
|View full text |Cite
|
Sign up to set email alerts
|

Impact of front line demonstrations on the production and productivity of moong (Vigna radiata L), mash (Vigna mungo L), rajmash (Phaseolus vulgaris L), lentil (Lens culinaris L) and chickpea (Cicer aeritinum L) under rainfed ecology in mid hills of J and K, India

Abstract: Pulses productivity in Jammu Kashmir, India, in North-Western (NW) Himalayas is far less than the national averages because of poor crop management cultivation of low yielding varieties. Frontline demonstration (FLD) program is an effective technology transfer tool for better technology adoption that bridges the yield gaps. The technological extension yield gaps in pulses crops were studied for 3 years during 2009-10 to 2013-2014 under an FLD programme in the Poonch District of Jammu Kashmir, India, revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…It indicates that there exists a gap between the generated technology in mung cultivation at the research institution and its dissemination to the farmers. Kumar et al (2019) reported as high as 55.00-70.85 percent technology index in their study.…”
Section: Technology Indexmentioning
confidence: 71%
See 2 more Smart Citations
“…It indicates that there exists a gap between the generated technology in mung cultivation at the research institution and its dissemination to the farmers. Kumar et al (2019) reported as high as 55.00-70.85 percent technology index in their study.…”
Section: Technology Indexmentioning
confidence: 71%
“…Kumar et al (2017) also found similar results. Kumar et al (2019) also reported yield enhancement of 30.90 percent over farmers' practice in Poonch district of Jammu and Kashmir while conducting FLDs with the variety SML-818. Kumar and Boparai (2020) conducted demonstrations with improved varieties SML 668 and SML 832 in Jalandhar district and found that demonstrations conducted after harvest of potato and sown in the month of March produced mean yield of 10.48 q/ha.…”
Section: Analysis Of Yield Gapmentioning
confidence: 94%
See 1 more Smart Citation
“…Yield of a particular crop on the given farm Production efficiency = - ----------------------------------× Other researchers use similar methodologies to assess the gaps in production efficiency and yield (Sharma et al 2015;Vaid et al 2017;Arora and Sharma 2019;Kumar et al 2019).…”
Section: Production Efficiency and Yield Gapsmentioning
confidence: 99%
“…Improved chickpea varieties hold a key for improving production and productivity of the crop (Kassie et al, 2009;Patil and Ramesha, 2018). Besides, according to Kumar et al (2019) the technological yield gaps affecting yield in pulses were highest in chickpea. This paper is, therefore, aimed to provide an insight into scaling up of chickpea technologies and documenting best approaches to maximize production and productivity of the crop through improving the availability of improved quality seeds to farmers.…”
Section: Introduction Background: Chickpea Production In Ethiopiamentioning
confidence: 99%